Gerak Photon dalam Medan Gravitasi jang Kuat disekitar Bintang jang Mampat. - Winardi Sutantyo (Institute for Research and Community Services (LPPM) ITB, 1971)
Ringkasan. Dalam tulisan ini, review mengenai gerak photon dalam medan gravitasi jang kuat diberikan. Photon jang dipantjarkan dari sekitar atau dalamnja sebuah bintang jang sangat mampat dapat lepas, djatuh kembali, atau bergerak dalam orbit lingkaran, bergantung pada arah mula2 dari ketjepatan photon. Abstract. In this paper, a review of the motion of photons in a strong gravitational field is given. Photon which are emitted from the neighborhood or from within a superdense star, may escape, falling or moving in a circular orbit, depending on the initial direction of the photons.